Iliac artery false aneurysm twelve years after allograft nephrectomy - Guimarães Rosa, Nuno; Silva, Sónia; Jorge, Sofia; Branco, Patricia; Inácio, João; Barbas, José; Gomes da Costa, A; Martins Prata, M (SPN- Sociedade Portuguesa de Nefrologia, 2007)
We report a case of a non-infected right external iliac artery false aneurysm. The patient was a 44 year-old woman on chronic peritoneal dialysis had had an allograft nephrectomy 12 years before and who presented with acute abdominal pain. Ultrasound and CT-scan showed a saccular aneurysm arising from the right external iliac artery. A large false aneurysm was identified during surgery, from donor arterial vessel remaining in situ after graft nephrectomy. Resection of the false aneurysm, with ligation of the right external iliac artery and interposition of a femorofemoral graft was successfully performed, with an uneventful post-operative recovery. False aneurysms after renal allograft nephrectomy are very rare. To our knowledge, this is the longest reported period of time between na nephrectomy and clinical evidence of a false aneurysm.
Keywords: False-aneurysm; iliac artery; Kidney transplantation; Madeira Island; Portugal; Região Autónoma da Madeira